The axisymmetric shrink fit problem subjected to axial force - Lopes, J; Hills, D; Paynter, R (Elsevier, 2018)
A solution for the stress fields in a shaft-hub shrink-fit assembly subjected to an axial force is presented. The assembly is modelled as a semi-infinite shaft embedded within an elastic half-space. The stress field for a bilateral solution is obtained, considering that the contact interface is everywhere subjected to pressure and that the coefficient of friction is sufficient to prevent slip everywhere. This solution is then corrected to satisfy the slip condition using an array of strain nuclei in the form of glide ring dislocations. The contact pressure, shear traction and their ratio is presented as a function of the coefficient of friction and the ratio of shrink-fit to axial force stresses. Finally, the solution is extended to a finite shaft.